A Chain-Ladder Analysis of P&I Claims - 2021 - Berketis, Nicholas G. (Archives of Business Research, 2023)
According to the latest Market Review for 2021/2022 prepared by Lockton: The latest financial results from the International Group of P&I Clubs suggests that we are now in the full swing of a hardening market with premium rises due to be requested over the next year or, perhaps, longer – whether this be due to individual Club performance or the renewal of the International Group General Excess of Loss programme, or both.